Analgesic efficacy of intra-peritoneal instillation of dexamethasone and bupivacaine versus bupivacaine following laparoscopic cholecystectomy – A randomised, double-blind controlled study - Pakhare Vandana; Nanda Ananya; D Muralikrishna; Supraja Ponduru; Vyshnavi Renganathan; Ramchandran Gopinath (Indian Journal of Anaesthesia, 2023)
Background and Aims: Laparoscopy is associated with acute pain. We compared the effectiveness of intra-peritoneal dexamethasone with bupivacaine versus bupivacaine in patients undergoing laparoscopic cholecystectomy for postoperative analgesia. Methods: This randomised study was conducted after approval from the institutional ethics committee and 84 patients were randomly allocated into bupivacaine with dexamethasone group (BD) (received 40 mL of 0.25% bupivacaine with 16 mg dexamethasone), and bupivacaine group (BB) (received 40 mL of 0.25% bupivacaine intra-peritoneally). Data analysis was done using R version 4.2.1. The visual analogue scale (VAS) score, total rescue analgesic dose, and time required for the first analgesic between groups were compared using the Wilcoxon rank sum test or t-test appropriately. Results: VAS score was significantly lower in the BD group compared to the BB group until 2 h post-operatively with a mean difference of − 1.0 (95% confidence interval [CI] −1.5, −0.53), P < 0.001. The total rescue analgesic dose consumed was lower in the BD group (60.71 mg [29.80]) compared to the BB group (73.20 mg [11.57]) with a mean difference of − 12.5 mg (95% CI − 22.3, −2.68), P = 0.013. In addition, the time taken for the requirement of the first rescue analgesic was significantly longer in the BD group (417.1 min [276.0]) compared to the BB group (219.4 min [226.1]) with a mean difference of 197.7 (95% CI 75, 320), P = 0.002. Conclusion: Intra-peritoneal instillation of 16 mg dexamethasone with 0.25% bupivacaine in laparoscopic cholecystectomy significantly reduces post-operative pain and requirement of rescue analgesic compared to 0.25% bupivacaine alone.